”Don’t Say Gay” : Critical Discourse Analysis on Discursive Structures and Ideologies in U.S. News Coverage of Florida’s “Parental Rights in Education” Bill - Rauha, Aapo (My University, 2023)
This thesis examines the discourse in U.S. online newspapers about the Parental Rights in Education bill, which passed Florida legislation in March of 2022 and took effect in June of the same year. The bill is labelled as controversial by many media and criticised for being anti-LGBT+. This study uses Critical Discourse Analysis and focuses on the social issues of comprehensive sexuality education and media impact and transparency. Using corpus-collected data of 50 online news articles, this thesis aims to find out what kind of language elements related to sexuality education and related legislation are found in the data and what ideologies these elements indicate. The study also examines directness and indirectness in the language. The methods of the study are modelled and modified after the works of Reisigl and Wodak and van Dijk. The analysis is done manually by reading the data and applying techniques of close reading and examining the language and its broad meanings. The study aims for a triangulated perspective, meaning that the analysis considers not only the findings but also theoretical background and situational, political, and cultural context. The findings of the study show that ideologies are present in the news discourse. Considering the social issue, this thesis argues that comprehensive sexuality education is vital for children’s well-being, and media reporting about such topics have power in how they are perceived, as well as how topic-related laws are interpreted.
Keywords: Critical discourse analysis, Ideology, Florida, LGBT+, Don’t Say Gay, Parental rights in Education, News on the Web Corpus